From crisis to recovery the causes, course and consequences of the great recession - Keeley, Brian; Love, Patrick 1955- (OECD Insights., 2010)
How did the sharpest global slowdown in more than six decades happen, and how can recovery be made sustainable? This publication traces the causes, course and consequences of the "Great Recession". It explains how a global build up of liquidity, coupled with poor regulation, created a financial crisis that quickly began to make itself felt in the real economy, destroying businesses and raising unemployment to its highest levels in decades. The worst of the crisis now looks to be over, but a swift return to strong growth appears unlikely and employment will take several years to get back to pre-crisis levels. High levels of public and private debt mean cutbacks and saving are likely to become the main priority, meaning the impact of the recession will continue to be felt for years to come.--Publisher's description.